ANALISIS AKUNTANSI ASET TETAP PADA KOPERASI HMS - Hasanudin Hasanudin; Irawan Irawan; Dian Nirmala Dewi (Jurnal Ilmiah ESAI, 2021)
Fixed assets have an important role for the smooth running of cooperative operations. Proper policy in the treatment of fixed asset accounting is needed in maximizing that important role. Users of financial statements urgently need information in accordance with the Financial Accounting Standards of Entities Without Public Accountability (SAK ETAP) so that an analysis of fixed asset treatment needs to be done to ensure whether the treatment of fixed assets has been in accordance with the ETAP SAK. The data used is secondary data consisting of the financial statements (balance sheet) of THE HMS Cooperative in 2018, data on ownership of the 2018 HMS Cooperative fixed assets (list of equipment, vehicles and furniture) along with the list of depreciation of cooperative fixed assets 2018. In data analysis the methods used are qualitative and quantitative methods. Based on the results of the analysis, it can be concluded that the fixed assets in the HMS Cooperative have been in accordance with SAK ETAP No. 15. In the recognition of fixed assets, cooperatives recognize the type of fixed assets by means of their acquisition, namely by cash purchase. Hms's cooperative fixed assets are depreciated using the straight line method.  In termination, the HMS Co-operative has never stopped its fixed assets. HMS cooperative complies with SAK ETAP in its presentation, where fixed assets are presented in the balance sheet. However, HMS Cooperative does not disclose fixed assets because the cooperative does not make CALK